Dysfunction of endoscopic third ventriculostomy in children - Luciano Lopes Furlanetti (Brazilian Society for Pediatric Neurosurgery, 2019)
Introduction: Neuroendoscopy is particularly useful as an adjunct in the treatment of hydrocephalus. CSF physiology differs among neonates, children and adults leading to different and conflicting results in the treatment of hydrocephalus using neuroendoscopy. The aim of our study was to review the literature regarding to analyze predictive clinical and imaging models available and discuss specific aspects of the endoscopic approach to hydrocephalus in infants